Testing the Kerr Metric with X-Ray Reflection Spectroscopy of Mrk 335 Suzaku Data - Choudhury, Kishalay; Nampalliwar, Sourabh; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier (Astrophysical Journal, 2019)
Einstein's gravity has undergone extensive tests in the weak field gravitational limit, with results in agreement with theoretical predictions. There exist theories beyond general relativity (GR) which modify gravity in the strong field regime but agree with GR in the weak field. Astrophysical black holes are believed to be described by the Kerr metric and serve as suitable candidates to test strong gravity with electromagnetic radiation. We perform such a test by fitting one Suzaku data set of the narrow-line Seyfert 1 (NLS1) galaxy Mrk 335 with X-ray reflection spectroscopy, using the Johannsen metric to model the black hole spacetime and test for deviations from Kerr. We find the data is best modeled with a hybrid model that includes both partial covering absorption and a reflection component. This is the first time such a model has been proposed for a high-flux (low reflection) Mrk. 335 data set. We constrain the Johannsen deformation parameter alpha(13) to 1.5 < alpha(13) < 0.6 with spin parameter a(*) > 0.8, and the alpha(22) parameter to -0.4 < alpha(22) < 2.1 with a(*) > 0.7, both at the 99% confidence level. Although additional solutions at large deviations from the Kerr metric show statistical similarity with the ones above, further analysis suggests these solutions may be manifestations of uncertainties beyond our control and do not represent the data. Hence, our results are in agreement with the idea that the supermassive compact object at the center of Mrk 335 is described by the Kerr metric.
CRIS-Team WoS Importer:2019-07-26